Adult MOOC Learners as Self-Directed: Perceptions of Motivation, Success, and Completion - Jamie Loizzo; Peggy A. Ertmer; William R. Watson; Sunnie Lee Watson (Online Learning, 2017)
Despite the increased attention given to MOOCs over the last four years, learners’ voices have been noticeably absent. This virtual ethnographic study was designed to examine the experiences of 12 adult learners with bachelors’ and masters’ degrees, enrolled in a four-week MOOC on the topic of human trafficking. Through the lenses of self-directed learning and self-determination theories, we were interested in investigating learners’ motivations for enrolling in the MOOC, their perceptions of success and completion, and barriers encountered while trying to complete the MOOC. Reasons for enrollment varied from personal enjoyment to professional development, and differing definitions emerged regarding completion or success in a MOOC. Implications of this study include a proposed conceptual framework of adult learner MOOC motivations and goals, which may inform the intentional instructional design of MOOCs to better meet adults’ self-directed learning needs. Results also pointed to the potential for social science MOOCs to promote activism and attitudinal and social change.